Mirna Expression in Glaucomatous and TGFβ2 Treated Lamina Cribrosa Cells - Lopez, Navita N. (Int J Mol Sci, 2021)
Glaucoma is a group of optic neuropathies that leads to irreversible vision loss. The optic nerve head (ONH) is the site of initial optic nerve damage in glaucoma. ONH-derived lamina cribrosa (LC) cells synthesize extracellular matrix (ECM) proteins; however, these cells are adversely affected in glaucoma and cause detrimental changes to the ONH. LC cells respond to mechanical strain by increasing the profibrotic cytokine transforming growth factor-beta 2 (TGFβ2) and ECM proteins. Moreover, microRNAs (miRNAs or miR) regulate ECM gene expression in different fibrotic diseases, including glaucoma. A delicate homeostatic balance between profibrotic and anti-fibrotic miRNAs may contribute to the remodeling of ONH. This study aimed to determine whether modulation of miRNAs alters the expression of ECM in human LC cells. Primary human normal and glaucoma LC cells were grown to confluency and treated with or without TGFβ2 for 24 h. Differences in expression of miRNAs were analyzed using miRNA qPCR arrays. miRNA PCR arrays showed that the miR-29 family was significantly decreased in glaucomatous LC cell strains compared to age-matched controls. TGFβ2 treatment downregulated the expression of multiple miRNAs, including miR-29c-3p, compared to controls in LC cells. LC cells transfected with miR-29c-3p mimics or inhibitors modulated collagen expression.